Rearranged diterpenoids from the biotransformation of ent-trachyloban-18-oic Acid by Rhizopus arrhizus - Leverrier, A.; Martin, Marie-Therese; Servy, C.; Ouazzani, J.; Retailleau, P.; Awang, Khalijah; Mukhtar, M.R.; Gueritte, F.; Litaudon, M. (American Chemical Society, 2010)
In our search for inhibitors of the antiapoptotic protein Bcl-xL, investigation of Xylopia caudata afforded a new diterpenoid, ent-trachyloban-4 beta-ol (2), and five known ent-trachylobane or ent-atisane compounds. Only ent-trachyloban-18-oic acid (1) exhibited weak binding activity to Bcl-xL. These compounds exhibited cytotoxicity against KB and HCT-116 cell lines with IC(50) values between 10 and 30 mu M. Bioconversion of compound 1 by Rhizopus arrhizus afforded new hydroxylated metabolites (3-7) of the ent-trachylobane ancl ent-kaurene type;aid compound 8, with a rearranged pentacyclic carbon framework that was named rhizopene. Compounds 3-8 were noncytotoxic to the two cancer cell lines, and compounds 3 and 5 exhibited only weak binding affinity for Bcl-xL.